Über die Identität von Lyonetia hygrophilella (Viette, 1957) comb. nov. [Chrysoclista] (Lepidoptera: Lyonetiidae), ihrer primären Stadien und Futterpflanzen - Bippus, Maik (Contributions to Entomology = Beiträge zur Entomologie, 2017)
Lyonetia hygrophilella (Viette, 1957) [Chrysoclista] comb. nov. is redescribed and transferred to Lyonetiidae. This species mines the leaves of Syzygium cumini (L.) Skeels (Myrtaceae). The larval stages, adults, and genitalia are illustrated and described.